2022
DOI: 10.3389/fimmu.2022.947213
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional regulatory feedback encodes JAK-STAT signal memory of interferon stimulation

Abstract: Immune cells fine tune their responses to infection and inflammatory cues. Here, using live-cell confocal microscopy and mathematical modelling, we investigate interferon-induced JAK-STAT signalling in innate immune macrophages. We demonstrate that transient exposure to IFN-γ stimulation induces a long-term desensitisation of STAT1 signalling and gene expression responses, revealing a dose- and time-dependent regulatory feedback that controls JAK-STAT responses upon re-exposure to stimulus. We show that IFN-α/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…One of the examples of such work can be found in [116] , where the authors suggested that in order to explain experimental results activation of some phosphatase, not yet identified, is needed. That was confirmed much later [14] , and that finding, in turn, allowed to develop a new model explaining JAK-STAT network's ability to decode relative changes of dose, timing, and type of temporal interferon stimulation [59] .…”
Section: Success Storiesmentioning
confidence: 68%
“…One of the examples of such work can be found in [116] , where the authors suggested that in order to explain experimental results activation of some phosphatase, not yet identified, is needed. That was confirmed much later [14] , and that finding, in turn, allowed to develop a new model explaining JAK-STAT network's ability to decode relative changes of dose, timing, and type of temporal interferon stimulation [59] .…”
Section: Success Storiesmentioning
confidence: 68%
“…These included the highly variable and abundant genes including chemokine family Ccl5, Ccl4, Ccl3, Ccl2 as well as IL1b and TNFa. While the scRNA-seq can be in principle treated as time-series data (e.g., across the replicates from individual mice) [34], our current understanding of TLR signalling suggest that due to endotoxin resistance and desensitisation [56][57][58], the regulatory network, and thus model structures and parameters, are time-varying rather than stationary [59]. We therefore treated each data time-point (and replicate) separately, which also allowed more efficient implementation to fit 1,507 mouse, and 1,079 orthologue conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Beta-Poisson fits, we selected 96 high coverage murine response genes (and 28 orthologue genes for species analyses), which have existing estimates of mRNA half-life in LPS-stimulated bone marrow derived macrophages ( Hao and Baltimore, 2009 ; Kratochvill et al, 2011 ) or other cell models. Our current understanding of TLR signalling suggest that due to endotoxin resistance and desensitisation ( Buckley et al, 2006 ; Morris et al, 2014 ; Kalliara et al, 2022 ), the regulatory network, and thus model structures and parameters, are time-varying ( Wang et al, 2018 ). For example, previous work show that stability of TLR target genes are regulated in response to stimulation, and also may vary between treatments ( Hao and Baltimore, 2009 ).…”
Section: Discussionmentioning
confidence: 99%